Diacetylated and acetone-conjugated flavan-3-ols as potent antioxidants with cell penetration ability. (January 2015) - Meng, Hao-Cong; Gao, Jie; Zheng, Hua-Chuan; Damirin, Alatangaole; Ma, Chao-Mei
Highlights: Acetylated or acetone-conjugated flavan-3-ols were prepared. The 3, 5 or 3, 7- O -diacetyl flavan-3-ols have high cell penetration ability. The diacetyl flavan-3-ols released free flavan-3-ols in cells. Acetone conjugates of flavan-3-ols entered into cells in intact form. The derivatives protected oxidative hemolysis more effectively than flavan-3-ols. Abstract: Catechin and epicatechin are the health beneficial flavan-3-ols in tea and many fruits. However, their extreme hydrophilicity renders drawbacks for them to pass through the bio-membranes. We prepared lipophilic flavan-3-ol derivatives by acetylation or by acetone-conjugation. The structures of these derivatives were determined based on their NMR and MS spectra. The 3, 5- and 3, 7-diacetyl derivatives showed radical scavenging activity slightly weaker than catechin and epicatechin, but showed significantly enhanced capacity to penetrate into living cells. Moreover, the diacetyl derivatives released flavan-3-ols inside cells, while catechin or epicatechin themselves could not penetrate into the cells. The acetone conjugates showed strong antioxidant activity and were able to enter into living cells in the intact form. The acetylated and acetone-conjugated derivatives protected H2 O2 -induced erythrocyte hemolysis more effectively than catechin and epicatechin. These results indicated that acetylated and acetone-conjugated flavan-3-ols are promising compounds with less hydrophilicity and better bioactivities in biological systems.